Development and validation of the HPLC analysis method for stability study of extemporaneous rifampicin syrup prepared by Hospital Putrajaya / Norsyahida Mat Yasin - Mat Yasin, Norsyahida (2013)
ifampicin has been used widely to treat infection caused by Mycobacterium Tuberculosis. It exhibits its action by inhibiting-dependant RNA polymerase in bacteria. The aim of this study is to develop and validate a high-performance liquid chromatography (HPLC) quantitative analysis method in order to be utilized in the future to assess the stability of rifampicin syrup prepared by Hospital Putrajaya. The HPLC system with UV detector with wavelength 254 nm was used. The column is Eclipse XDB-C18 (4.6 mm x 150 mm, 5µm). The mobile phase is 65% of 0.01 M of potassium phosphate buffer pH 5 and 35% of acetonitrile. The flow rate of mobile phase is 1 ml/min. the volume of sample injection is 20 µL. Six different concentrations of rifampicin solution were used to develop calibration curves. Correlation coefficient that was obtained is greater than 0.99. Therefore, it can be considered that the curves have very good linearity. Furthermore, the accuracy and precision values meet the FDA requirement. So, this method can be utilized in the future to assess the stability of rifampicin syrup prepared by Hospital Putrajaya.